Pengaruh Viralitas di Media Sosial terhadap Penegakan Hukum di Indonesia - Ginting, Wina Br; Prabowo, Anisa; Arianti, Raras Santika; Savana, Lintang; Kamal, Ubaidillah Santika (Jurnal Ilmiah Wahana Pendidikan, 2025)
Social media has significantly transformed public participation in law enforcement processes in Indonesia. This study aims to examine how the virality of content on social media platforms influences the response of legal institutions to violations of the law. Employing a qualitative approach through library research, the study seeks a comprehensive understanding of this phenomenon. Findings indicate that viral content can accelerate law enforcement actions; however, it may also lead to inequality, as cases that do not gain widespread attention often receive less serious consideration. Therefore, this article emphasizes the importance of balancing social media influence with the principle of equality before the law to ensure fair and equitable justice. Recommendations are made to develop a more adaptive and inclusive law enforcement system in the digital era.